The art of Toshiko Takaezu in the language of silence - Held, Peter 1951-; Takaezu, Toshiko 1922-2011 (Univ. of North Carolina Press, 2010)
Presents a series of essays about the life and accomplishments of the Japanese American artist, describing her work as a potter, her incorporation of Eastern and Western techniques, and her transition into abstract sculpture and installation art
Introduction and acknowledgments / Peter Held -- Foreword / Jack Lenor Larsen -- Toshiko Takaezu : six decades / Paul J. Smith -- "An unsaid quality" / Janet Koplos -- Life touchstones / Donald Fletcher -- A tribute / Jeff Schlanger -- Chronology / Jeffrey Spahn
Includes bibliographical references (p. 158-159) and index
Keywords: Takaezu, Toshiko; Takaezu, Toshiko -- 1922-2011; Geschichte 1900-2000; Art pottery, American / 20th century; Art pottery, American / 21st century; American pottery / History; American pottery / Biography; Geschichte; Keramik; Bildband; Biografie